RADIO FREQUENCY IDENTIFICATION (RFID):ADVANCEMENTS, APPLICATIONS, ANDSECURITY CHALLENGES - Nagaraju Arthan; Goutham Kacheru; Rohit Bajjuru (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2025)
Radio Frequency Identification or RFID is one of the essential components of automated data capturing and wireless identification, and in 2020 this technology evolved significantly, giving a new push to its implementation in various industries. This survey presents various developments in passive and active RFID systems with improvements on range, power consumption, and data processing ability. Ultra-highfrequency (UHF) tags for passive RFID experienced many innovations, including wider read ranges and reduced power requirements while active RFID systems improved battery longevity as well as real-time tracking capabilities.RFID applications were much wider in 2020, especially under its implementation in the supply chain that recruites real-time warehouse tracking, enhanced logistics and less operational inefficiencies. In healthcare, the RFID kept track of patients, medical assets and pharmaceutical supplies to help ensure compliance and minimize errors. It is also an integral technology in security and access control, offering solution for identity verification and anti-counterfeiting.However, the speedy acceleration of RFID face numerous security risks and privacy issues: unauthorized scanning, data breaches, risk of tag cloning. This review analyzes these issues in addition to novel solutions such ascryptographic protocols, secure authentication mechanisms, and privacy-preserving designs. The trends, applications and security challenges are identified and examined analysing where RFID stands in 2020 and where it can grow further boosting innovativesolutions.